Optimasi Pembagian Tugas Dosen Pengampu Mata Kuliah Dengan Metode Particle Swarm Optimization - Muhammad Abduh; Rekyan Regasari Mardi Putri; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
In forming a lectures schedule, an absolute thing that had to be done is division of labor teaching duties in accordance with their field in order to create an effective teaching and learning activities. At Faculty of Computer Science (FILKOM) Brawijaya University, the assignment process is still manually designed where it requires some substantial time, therefore it needed a right optimization methods in dealing with this case. This problem can be solved by a population-based heuristic methods, Particle Swarm Optimization (PSO) which has been applied in various fields such as scheduling and assignments. The data used in this study is the data division of lecturers teaching tasks as a priority of lecturer's teaching interests to a course. Through the obtained results, it had tested to find the effect of tested parameters on the resulted fitness values. From PSO parameters test results, it obtained the best particle number as 100, best iteration number as 100, and combination of velocity parameter c1 and c2 as 1.5 and 1.5 with resulted fitness value as 94878. From the results of system, the obtained assignment solution gives good results, which is still within the limits of tolerance with decreasingly obtained error values in putting a lecturer on courses that according to their interests.